Fast Obstacle Distance Estimation using Laser Line Imaging Technique for Smart Wheelchair - Fitri Utaminingrum; Hurriyatul Fitriyah; Randy Cahya Wihandika; M Ali Fauzi; Dahnial Syauqy; Rizal Maulana (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This paper presents an approach of obstacle distance estimation for smart wheelchair. A smart wheelchair was equipped with a camera and a laser line. The camera was used to capture an image from the environment in order to sense the pathway condition. The laser line was used in combination with camera to recognize an obstacle in the pathway based on the shape of laser line image in certain angle. A blob method detection was then applied on the laser line image to separate and recognize the pattern of the detected obstacles. The laser line projector and camera which was mounted in fixed-certain position ensured a fixed relation between blobs-gap and obstacle-to-wheelchair distance. A simple linear regression from 16 obtained data was used to respresent this relation as the estimated obstacle distance. As a result, the average error between the estimation and the actual distance was 1.25 cm from 7 data testing experiments. Therefore, the experiment results show that the proposed method was able to estimate the distance between wheelchair and the obstacle.